HUBUNGAN ANTARA PERAN ORANG TUA DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Lisna Marwani (Akademika : Jurnal Teknologi Pendidikan, 2017)
The objective of the research is tof find out the relationships between the roleparents and disciplines learning with learning outcomes in civicpancasila educationlearning at the SMPN Bekasi. The Study was designed as a survey seventy five students, thatwere randomly selected were involved in the study. Simple and double regression andcorrelation procedure were used in the data analysis.The results of the study pointed outthat : (1) there was a positive and significance relationship between the role parents withthe learning outcomes in civic pancasila education, (2) there was a positive andsignificance relationship between disciplines learning with the learning outcomes in civicpancasila education; (3) there was positive and significance relationship between the roleparents and disciplines learning with together the learning outcomes in civic Pancasilaeducation.Therefore , it could be concluded that the higher the role parents and learningdisiciplines the higher learning outcomes in civic Pancasila education